Tingkat Pengetahuan, Sikap, dan Persepsi Mengenai Epilepsi antara Masyarakat Pedesaan dan Perkotaan di Padang - Hendra Permana (Health and Medical Journal, 2021)
Introduction: The Knowledge, perception and attitude about epilepsy in developing country, including Indonesia is still low. These problems can cause stigma and discrimination to the patient. Society still has the view that epilepsy is not a disease, but because of the inclusion of evil spirits, possessions, witches or a curse. Furthermore, the information gap between rural and urban society could contribute to the issues. Aims: This study was aimed to explore the knowledge, perception and attitude about epilepsy between rural and urban society in Padang. Method: This study used cross sectional comparative design. This study was conducted on February – June 2018 at Ulak Karang (urban) and Bungus (rural) public health center. The subjects of this study were 140 visitors of both public health centers. The inclusions criteria of this study was all visitors ≥ 17 years old and the exclusion criteria was all incomplete data. Data was taken by using questionnaire with 13 close questions. These data was analyzed with SPSS 22. Mannwhitney tests and Chi Square test were used to compare the knowledge, perception and attitude from the two groups. A P value below 0.05 was considered asstatistically significant. Result: From demographic data, there were no significant differences between urban and rural communities. In terms of knowledge about epilepsy, there are significant differences regarding the causes of epilepsy with a value of p = 0.002. In addition, perceptions of epilepsy stigma that differed significantly in urban and rural communities were regarding malformations in epilepsy patients with p = 0.046. As for community attitudes towards epilepsy patients, there were no significant differences between urban and rural areas Conclusion: Stigma is a frightening thing for people with epilepsy, because it can interfere with their social interactions and also reduce the opportunity to get a job and also the opportunity to get married.